Waste Operational Budget Before And After The Pandemic At The Kramatwatu Sub-District Office - Luhiyah Luhiyah (Review of Accounting and Taxation, 2022)
Purpose - The formulation of the problem in this study is whether the operational budget for waste before the pandemic is bigger than after the pandemic and vice versa at the kramatwatu sub-district office. The purpose of this study was to find out whether the operational budget for waste before the pandemic was bigger than after the pandemic and vice versa at the kramatwatu sub-district office. Design/methodology/approach - This research uses a writing method using a descriptive method according to sugiono, a method used to make broader conclusions. Using the descriptive method focusses on the problems that exist should be actual problems. Data collection is done by interview process, direct observation, and documentation. Finding - The results of this study indicate that after the covid19 outbreak, the revenue from the waste operational budget has increased at the kramatwatu sub-district office. Originality -